Spatial and bodily metaphors in narrating the experience of listening to sad music. (September 2014) - Peltola, Henna-Riikka; Saresma, Tuija
This study focuses on the affective experiences of listening to self-identified sad music. Previous studies have concentrated on the emotions induced by music by rationalizing and labelling emotions. However, focusing on such categorization leaves the subjective experiences of the individual aside. The aim of this article is to broaden the methodology of studying music and emotion by analysing the metaphorical language used in the narratives about the subjective experience of listening to music. A total of 373 participants answered open-ended questions about the experiences of listening to sad music via an online survey. The responses were then analysed using systematic thematic analysis concentrating on the metaphors used in participants' narratives. The aim was to identify interesting themes not usually attainable through conventional self-report methods. The analysis thus focused on how affective experiences were narrated, and what kinds of metaphors and metonymies were used in describing them. The narratives were put into two categories: (I) spatial metaphors, and (II) metaphors of movement. The analysis also showed similarities in metaphorical mappings of the listening experience and its conceptualization by individuals.